2018
DOI: 10.5395/rde.2018.43.e28
|View full text |Cite
|
Sign up to set email alerts
|

Triple antibiotic paste: momentous roles and applications in endodontics: a review

Abstract: This study investigated the latest findings and notions regarding ‘triple antibiotic paste’ (TAP) and its applications in dentistry, particularly endodontics. TAP is a combination of 3 antibiotics, ciprofloxacin, metronidazole, and minocycline. Despite the problems and pitfalls research pertaining to this paste has unveiled, it has been vastly used in endodontic treatments. The paste's applications vary, from vital pulp therapy to the recently introduced regeneration and revascularisation protocol. Studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
56
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 102 publications
(145 reference statements)
2
56
0
3
Order By: Relevance
“…It is necessary to note that methylcellulose is neutral and does not interfere with the transfer of the drug into the dentinal tubules of the tooth and is easily cleansed inside the root of the tooth. 12 The findings of this study on the use of MTAP against E. faecalis are similar to those of the ones conducted before this study. For instance, examining the antimicrobial effect of different concentrations of TAP in the first, second, third, and fourth weeks on the mature biofilm of E. faecalis, Frough Reyhani et al indicated that TAP in the concentrations of 10, 100 and 1000 mg/mL completely stymied the growth of bacteria, but at the concentrations of 1, 0.1 and 0.01 mg/mL, bacteria were not destroyed completely; however, in the comparison between these concentrations and the control group, it was noted that these concentrations showed remarkable antibacterial features.…”
Section: Discussionsupporting
confidence: 83%
“…It is necessary to note that methylcellulose is neutral and does not interfere with the transfer of the drug into the dentinal tubules of the tooth and is easily cleansed inside the root of the tooth. 12 The findings of this study on the use of MTAP against E. faecalis are similar to those of the ones conducted before this study. For instance, examining the antimicrobial effect of different concentrations of TAP in the first, second, third, and fourth weeks on the mature biofilm of E. faecalis, Frough Reyhani et al indicated that TAP in the concentrations of 10, 100 and 1000 mg/mL completely stymied the growth of bacteria, but at the concentrations of 1, 0.1 and 0.01 mg/mL, bacteria were not destroyed completely; however, in the comparison between these concentrations and the control group, it was noted that these concentrations showed remarkable antibacterial features.…”
Section: Discussionsupporting
confidence: 83%
“…TAP is another combination of antibiotics which was introduced especially for the regeneration and revascularization protocol and the treatment of open apex teeth with necrotic pulp. It has been also used in endodontic therapy, its application as an intracanal medicament has reported high antibacterial efficacy (9) . TAP consists of ciprofloxacin, metronidazole, and doxycycline which all act against the pathogens commonly found inside the root canal system including Enterococcus faecalis.…”
Section: Discussionmentioning
confidence: 99%
“…Triple antibiotic paste (TAP), which is a combination of three antibiotics, namely, metronidazole, ciprofloxacin, and minocycline, has been used as an intracanal medicament owing to its high antimicrobial effects [31]. There is a controversy between the studies supporting its efficacy to eradicate EF in the root canal system completely [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%